Machining Difficult-to-Cut Materials Basic Principles and Challenges - Kishawy, Hossam A.; Hosseini, Ali (Materials Forming, Machining and Tribology,, 2019)
This book focus on the challenges faced by cutting materials with superior mechanical and chemical characteristics, such as hardened steels, titanium alloys, super alloys, ceramics and metal matrix composites. Aspects such as costs and appropriate machining strategy are mentioned. The authors present the characteristics of the materials difficult to cut and comment on appropriate cutting tools for their machining. This book also serves as a reference tool for manufacturers working in industry.